Imputacja i kalibracja jako remedium na braki odpowiedzi w badaniu budżetów gospodarstw domowych - Paradysz, Jan; Szymkowiak, Marcin (Imputation and Calibration as a Remedy for Nonresponse in Household Budget Surveys, 2007)
The main goal of the paper was to present theoretical and empirical aspects of imputation and calibration as standard methods of dealing with the lack of response in statistical surveys. The authors focused on Polish household budget surveys where the lack of participation of some of which is a significant problem. Because the lack of response occurs on a large scale, it influences the quality of the results. The authors showed how calibration estimators which were proposed by Sixten Lundström and Carl-Erik Särndal, can be used in order to improve estimations in Polish household budget surveys.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 74-81